Nutritional Status of Out-patient Hemodialysis Patients in a Hospital-based Hemodialysis Centre in Nepal - Khadka, Ruju; Basnet, Nabin Bahadur; Kafle, Rishi Kumar (Nepalese Medical Journal, 2018)
Introduction: Malnutrition is common among patients on chronic hemodialysis and is a risk factor. Nutritional assessment ensures early recognition and appropriate intervention. Dietary interview, physical and anthropometric measurements, biochemical assessment, bio-impedance, and structured assessment tools like subjective global assessment are modalities for identifying and monitoring of nutritional assessment of hemodialysis patients. This study was conducted to assess the nutritional status of hemodialysis patients and identify various factors related to malnutrition. Materials and Methods: A cross-sectional study of 72 chronic hemodialysis patients at a hemodialysis unit in Lalitpur was done. Detailed dietary and personal interview, anthropometric measurements, biochemical assessment, and subjective global assessment were used to collect the data to determine the prevalence of malnutrition among the hemodialysis patients as well as identify various factors related. Results: Malnutrition was prevalent among the respondents. The respondents were mostly male with average age of 50.2 1.9 years and majority being on hemodialysis for more than two years. Though severe malnutrition was absent among the hemodialysis patients assessed, mild to moderate malnutrition was seen in 52.78%. Most of these patients were female and were of older age group. Patients who had malnutrition had experienced a significant weight loss in previous six months. Anthropometric profile, dietary habits, and biochemical profile did not correlate with occurrence of malnutrition in hemodialysis patients. Conclusions: Malnutrition is fairly prevalent in chronic hemodialysis patients which can be identified by subjective global assessment. Elderly patients and patients who are losing weight are risk factors for mild to moderate malnutrition. Nepalese Medical Journal, vol.1, No. 1, 2018, Page: 12-16